A randomized, double-blind, phase II study of ramucirumab plus docetaxel vs placebo plus docetaxel in Japanese patients with stage IV non-small cell lung cancer after disease progression on platinum-based therapy. (September 2016) - Yoh, Kiyotaka; Hosomi, Yukio; Kasahara, Kazuo; Yamada, Kazuhiko; Takahashi, Toshiaki; Yamamoto, Nobuyuki; Nishio, Makoto; Ohe, Yuichiro; Koue, Toshiko; Nakamura, Takashi; Enatsu, Sotaro; Lee, Pablo; et al.
Highlights: We assessed second-line ramucirumab-docetaxel in Japanese patients with NSCLC. Ramucirumab-docetaxel PFS was longer than placebo-docetaxel PFS (HR 0.83). Febrile neutropenia was more common with ramucirumab-docetaxel (34.2% vs 19.8%). Exploratory group of EGFR-TKI-pretreated patients had similar results. Results in Japanese patients were similar to those seen in the REVEL trial. Abstract: Objectives: Ramucirumab plus docetaxel prolongs survival in patients with non-small cell lung cancer (NSCLC) with disease progression after platinum-based therapy. This phase II, double-blind, randomized, placebo-controlled study assessed efficacy and safety of second-line ramucirumab-docetaxel in Japanese patients with NSCLC. Materials and methods: Patients with NSCLC with progression after platinum-based therapy (28 Japanese sites; 19 December, 2012 to 22 May, 2015) were randomized (computer-generated sequence) to ramucirumab 10 mg/kg or placebo, followed by docetaxel 60 mg/m 2 (Day 1, 21-day cycle). Prior epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) monotherapy was prohibited in the primary population, but EGFR mutation-positive NSCLC patients who were treated with EGFR-TKI were enrolled as a separate exploratory population. Primary endpoint was progression-free survival (PFS); secondary outcomes included overall survival, tumor response rates, and safety. Investigator tumor assessments were used for the efficacy endpoints. Results: In the primary population (N = 160 randomized, n = 157 treated), median (95% CI) PFS was longer with ramucirumab-docetaxel (5.22 [3.52–6.97] months; n = 76) than with placebo-docetaxel (4.21 [2.83–5.62] months; n = 81); hazard ratio 0.83 (95% CI 0.59–1.16). Median (95% CI) overall survival was 15.15 (12.45–26.55) months with ramucirumab-docetaxel and 14.65 (11.93–24.44) months with placebo-docetaxel (hazard ratio [95% CI] 0.86 [0.56–1.32]). Objective response rate (28.9% vs 18.5%) and disease control rate (78.9% vs 70.4%) were numerically greater with ramucirumab-docetaxel than with placebo-docetaxel. Incidence and severity of most adverse events were similar, but febrile neutropenia was more common with ramucirumab-docetaxel (34.2%) than with placebo-docetaxel (19.8%). Conclusion: Second-line ramucirumab-docetaxel improved PFS similar to that seen in the REVEL trial with a manageable safety profile in Japanese patients with NSCLC.